Metacognição e estilos de aprendizagem: perspectivas educacionais na formação do psicólogo clínico - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Metacognition has as its definition the ability of the subject to know, monitor and self-regulate their internal processes, so that they learn to learn effectively and meaningfully. Learning styles, in turn, are the educational choices made by the learner to present their preferences for knowledge building. This study investigated the metacognitive strategies and learning styles through practical activities in the Psychology disciplines in the clinical area in different health contexts, from the Federal University of Amazonas / UFAM, in the city of Manaus. This is a cross-sectional, exploratory-descriptive, cross-sectional research. Thirty students (n = 30), assessed through the Learning Styles Assessment Scale (EAEA) and Focus Group (FG), were analyzed. There was a predominance of female participants (n = 21), between eighteen and twenty and fifty-four (18 ≥ 54). All participants reported being in clinical psychology with the majority in the approach of psychoanalysis (n = 10) in the 9th period (n = 21). Most (n = 23) declared themselves employed, performing paid internship as a function (n = 17). In the EAEA responses, the personal conditions dimension (56.7%) predominated, in which students report that they learn better by doing and recognize reading as a facilitator of their studies, followed by the dimension of environmental conditions (50%), where they stood out. that the bright and calm environment favors the study processes. Following, the answers highlighted the dimension of social conditions and activities (both with 43.3%), pointing out that group study, talking with colleagues about study subjects facilitate learning, as well as examples and practical exercises facilitate understanding of the subject in the classroom. As for instrumental conditions (40%), the students stated that the internet and computer use are resources that help in learning situations. As for the answers of the FG, five categories of analysis emerged derived from the students' statements. The first category refers to the didactic-pedagogical methodology of the course, having as subcategories the theoretical and practical training of teachers, correlation between the disciplines, less general training and research incentive; the second refers to the pedagogical didactic functioning of the Supervised Internship, subdivided into the role of the supervisor, the methodology adopted in the supervisions and the theoretical foundation necessary for the practice; The third category refers to the teacher-student relationship, having as subcategory the relationship with the teachers during the undergraduate course and with the internship supervisor; In the fourth category there are students' learning strategies, in the subcategories the study routine, learning self-perception, procrastination and distractions in the learning process and study practice techniques; The fifth category refers to the academic trajectory of the students, subdivided into contributions from the Supervised Internship, suggestions for changes in the functioning of the course, CSPA attendance space and concerns with the intern student's mental health. The data obtained answer the questions raised at the beginning of this study, understanding that the understanding of students' learning styles and metacognitive strategies established by them favor a meaningful learning throughout their formative process.
Keywords: Psicólogos clínicos; Metacognição; Aprendizagem; CIÊNCIAS HUMANAS: PSICOLOGIA; Estilos de aprendizagem; Metacognição; Formação do psicólogo; Psicologia clínica